Heterophase Photocatalysts from Water‐Soluble Conjugated Polyelectrolytes: An Example of Self‐Initiation under Visible Light. Issue 48 (8th October 2015) - Ghasimi, Saman; Prescher, Simon; Wang, Zi Jun; Landfester, Katharina; Yuan, Jiayin; Zhang, Kai A. I.
Abstract: We herein report a new design route to stable, heterophase photocatalysts, which function as highly dispersible conjugated polymer nanoparticles and porous monoliths under visible light in aqueous medium. They were constructed by attachment of the ionic‐liquid species 1‐alkyl‐3‐vinylimidazolium bromide onto the side chains of a photoactive polymer. The structure configuration allows not only photocatalysis in aqueous environment but also a unique self‐initiation radical cross‐linking process to transform the water‐soluble photoactive polymer into a heterophase system, either as nanoparticles or a porous monolith. High photocatalytic activity and reusability of the heterophase system were demonstrated in the degradation of organic dyes and reduction of Cr VI into Cr III in water under visible‐light irradiation. Abstract : Photoactive polymer‐based nanoparticles and porous materials were formed by the side‐product‐ and surfactant‐free self‐initiated cross‐linking of a conjugated polymer bearing vinylimidazolium side groups. The polymer acts as both a photosensitizer and a stabilizer for colloidal systems. The obtained cross‐linked polymers serve as efficient, recyclable, cost‐effective heterogeneous photocatalysts under visible‐light irradiation.